Dimensionamiento de la estructura de pavimento en la Calle 1 de San Isidro, Pérez Zeledón, utilizando la metodología mecanística empírica para diseño de pavimentos y creación de un plan de conservación - Murillo-Barboza, José Rafael (Instituto Tecnológico de Costa Rica, 2018)
To determine the structure of the pavement to be used in "Calle 1" of San Isidro, Pérez Zeledón the design of three types of flexible, semi-rigid, rigid pavements is proposed. These are designed by the mechanistic-empirical approach applying the graphic interface of "CR-ME" design of LanammeUCR in the cases of flexible and semi-rigid, and by reviewing performance models in the case of rigid. Layer thicknesses are evaluated from an AASHTO 93 design as a basis, and check of they meet the acceptance criteria that the models and the guides determine as acceptable for each type of pavement The materials and cost of the each design is quantified for their construction, and an analysis of each pavement is made, determining advantages and disadvantages through a SWOT matrix. In additim, an economic analysis using the RED model, where the initial investment cost and maintenance evaluated throughout the design period, allows to find the net real value and the internal rate of return. In addition, it is developed a maintenance plan that allows the Municipality of Pérez Zeledón the pavement and that the public sea the most benefit. With the above results most effective pavement design is found making sure it satisfies the needs required in Street 1, using the empirical mechanical methodology and proposing the maintenance required for this structure.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Pavimento; Costos; Factibilidad; Estructuras; Construcción